Economic Zeitgeist in Xi Jinping - Hailiang Gu (China Political Economy (CPE), 2018)
Purpose Xi Jinping's speech on the theme of "Continuously Exploring the New Zeitgeist of Marxist Political Economy in China," dated back to November 2015, has illuminated the historical background, social roots, practical basis, basic characteristics, Zeitgeist, ideological realm and other issues relative to the development of "Systematic Economic Theory" with Chinese characteristics (hereinafter referred to as SETCC). The paper aims to discuss these issues. Design/methodology/approach Exploring the SETCC marks a fundamental postulation for the development of contemporary Chinese Marxist political economy, and an important indicator of the Chinese wisdom thereof. Findings Unswervingly adhering to the new development concept as the leading factor, General Secretary Xi Jinping's elucidation of the theoretical propositions and practical topics of building a modern economic system has, starting from the five aspects of development mainline, strategic support, fundamental approach, necessary road and institutional guarantee, and their interrelationships, unfolded new connotations and opened up a new realm of Xi's New Economic Zeitgeist with new explorations on the structure and system of SETCC. Originality/value This paper first explains the development of Xi Jinping's economic thoughts and reveals its systematization characteristics.
Keywords: 330; Liberation and development of productive forces; Systematic economic theory; The "second coupling"; The new development concept